2008
DOI: 10.1016/j.radonc.2008.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-modulated radiation therapy (IMRT) for inoperable non-small cell lung cancer: The Memorial Sloan-Kettering Cancer Center (MSKCC) experience

Abstract: Introduction-Intensity-modulated radiation therapy (IMRT) is an advanced treatment delivery technique that can improve the therapeutic dose ratio. Its use in the treatment of inoperable non-small cell lung cancer (NSCLC) has not been well studied. This report reviews our experience with IMRT for patients with inoperable NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
79
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 38 publications
14
79
2
1
Order By: Relevance
“…The most likely explanation for the favorable results in our study is the high number of patients with early stage cancer. While 51.9% of all patients had stage Ⅰ/Ⅱ NSCLC in our study, patients with stage Ⅰ/Ⅱ NSCLC represented 0-27% of all patients in previously published studies (Yom et al, 2007, Sura et al, 2008, Liao et al, 2010, Govaert et al, 2012, Jiang et al, 2012. To confirm the favorable results of our study, additional studies with larger sample sizes and longer follow-up durations will be required.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The most likely explanation for the favorable results in our study is the high number of patients with early stage cancer. While 51.9% of all patients had stage Ⅰ/Ⅱ NSCLC in our study, patients with stage Ⅰ/Ⅱ NSCLC represented 0-27% of all patients in previously published studies (Yom et al, 2007, Sura et al, 2008, Liao et al, 2010, Govaert et al, 2012, Jiang et al, 2012. To confirm the favorable results of our study, additional studies with larger sample sizes and longer follow-up durations will be required.…”
Section: Discussionsupporting
confidence: 61%
“…Our study also showed favorable locoregional recurrence-free survival rate compared with previous studies. The 2-year locoregional recurrence-free survival rate was 64.5% in our study compared to the 50-58% reported in previously published studies (Yom et al, 2007, Sura et al, 2008, Jiang et al, 2012. The most likely explanation for the favorable results in our study is the high number of patients with early stage cancer.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…[25][26][27] The use of CRT can be insufficient for large and/or centrally located lesions or for patients who have widespread lymph node involvement and can lead to increased toxicity rates and the inability to reach an appropriate dose. [28][29][30] Liu et al demonstrated that IMRT could reduce the irradiated volumes of normal lung tissue and other critical structures significantly while maintaining an adequate dose to the target volume. 31 When the complexity of target volumes increases, the difference between CRT and IMRT becomes even more significant in favor of IMRT.…”
Section: Discussionmentioning
confidence: 99%